Estado fundamental do átomo de hidrogênio via equação de Dirac em um cenário com comprimento mínimo - Oakes, Thiago Luiz Antonacci (2013)
In this work we calculate the correction to the ground state energy of the hydrogen atom due to contribuitions arising from the presence of a minimal length. The minimal length scenario is introduced by means of modifying the Dirac equation truogh a deformed Heisenberg algebra (Kempf algebra). With the introduction of the Coulomb potential in the new Dirac energy Operator, we calculate the energy shift of the ground state of the hydrogen atom in first order of the parameter related to the minimal length via perturbation theory